Domestic violence: the discourse of women and men involved in criminal proceedings - Anderson Reis de Sousa; Nadirlene Pereira Gomes; Fernanda Matheus Estrela; Gilvânia Patrícia do Nascimento Paixão; Álvaro Pereira; Telmara Menezes Couto (Universidade Federal do Rio de Janeiro, 2017)
Abstract This qualitative, descriptive research had the purpose of analyzing the discourse of women and men involved in criminal proceedings on their experience of conjugal violence. Interviews were conducted with men in criminal proceedings for marital violence and the respective testimonies of their companions, contained in case files, were analyzed. Data were organized using the NVIVO® 11 software and the Collective Subject Discourse method. The discourses indicate that the reciprocity of the experience of violence is not recognized by the couple. While the woman sometimes transfers the responsibility of the act to the ingestion of alcohol or to herself, the man minimizes the event and questions the legitimacy of the testimony given by his companion. This points to the importance of the creation of spaces for reeducation in the perspective of gender, which would allow the recognition of the grievance by the couple and favor more respectful and harmonious relationships within the family.